Is money living? From Klossowski to finance money - Fumagalli, Andrea (Rivista Italiana di Filosofia del Linguaggio, 2023)
Starting from the text by Pierre Klossowski, the text analyses the role assumed by the “finance money”, once the relationship with gold ceased to exist following the collapse of the Bretton Woods system in 1971. In the new context of platform capitalism, where more and more acts of everyday life are commodified and put to value, financial markets become the engine of economic accumulation and the distribution of resources, capable of creating liquidity. Speculation activity, based on expectations, creates an ad hoc language: money becomes living: it is finance money which becomes symbolic and simulacrum, which tends to increasingly identify with 'money'. But with its triumph, the body dies.